2017
DOI: 10.1103/physreva.96.063820
|View full text |Cite
|
Sign up to set email alerts
|

Observing pure effects of counter-rotating terms without ultrastrong coupling: A single photon can simultaneously excite two qubits

Abstract: The coherent process that a single photon simultaneously excites two qubits has recently been theoretically predicted by [Phys. Rev. Lett. 117, 043601 (2016)]. We propose a different approach to observe a similar dynamical process based on a superconducting quantum circuit, where two coupled flux qubits longitudinally interact with the same resonator. We show that this simultaneous excitation of two qubits (assuming that the sum of their transition frequencies is close to the cavity frequency) is related to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 83 publications
0
30
0
Order By: Relevance
“…where the superscripts over the arrows indicate the polarizations of the electric fields. In the following calculations, we only consider the transitions from the lower band to the upper band because of the rotating-wave approximation [60,61] and initial condition. However, it has been shown that the counter-rotating terms will essentially influence the quantum dynamics in combination with some specific initial states [60,62].…”
Section:  D If Andmentioning
confidence: 99%
“…where the superscripts over the arrows indicate the polarizations of the electric fields. In the following calculations, we only consider the transitions from the lower band to the upper band because of the rotating-wave approximation [60,61] and initial condition. However, it has been shown that the counter-rotating terms will essentially influence the quantum dynamics in combination with some specific initial states [60,62].…”
Section:  D If Andmentioning
confidence: 99%
“…Therefore, such a non-classical phonon laser provides the key source for future fundamental studies and applications of quantum or nonlinear acoustics, such as vacuum Casimir-Rabi splittings [67] , squeezed phonons [68,69], and bistable phonon emission [70]. If the RWA is not satisfied, the pure effects [71] of counter-rotating terms should be observed. It is worth noting that the thermal noise of mechanical oscillators is detrimental for the coherent single phonon processes, while the negativity of the mechanical oscillator's Wigner function can still be observed with the thermal phonon occupation = n 2 th [66], which is corresponding to a 100 MHz mechanical mode in 10 mK environment.…”
Section: Phase-controlled Phonon Lasermentioning
confidence: 99%
“…One of the most interesting nonlinear optical effects predicted in the USC regime consists of the simultaneously excitation of two or more spatially separated atoms by a single photon [22][23][24]. This process is reversible, so that the atoms can return to a lower-energy state by collectively emitting one photon.…”
Section: Introductionmentioning
confidence: 99%